The final chapter of Vygotsky's Thinking and Speech: A reader's guide - van der Veer, Rene; Zavershneva, Ekaterina (My University, 2018)
The seventh and last chapter of Vygotsky's Thinking and Speech (1934) is generally considered as his final word in psychology. It is a long chapter with a complex argumentative structure in which Vygotsky gives his view on the relationship between thinking and speech. Vygotsky's biographers have stated that the chapter was dictated in the final months of Vygotsky's life when his health was rapidly deteriorating. Although the chapter is famous, its structure has never been analyzed in any detail. In the present article we reveal its rhetorical structure and show how Vygotsky drew on many hitherto unrevealed sources to convince the reader of his viewpoint.
Keywords: authorship; egocentric speech; inner speech; linguistics; vygotsky